ANALISIS KEBUTUHAN PELAYANAN BIMBINGAN KONSELING PADA MAHASISWA DI POLTEKKES KEMENKES RI PRODI KEPERAWATAN CURUP - Suriyanti, Suriyanti (CV. Lafadz Jaya, 2024)
The lack of counselors in tertiary institutions is a problem in the implementation of counseling service programs. Lack of support from each tertiary institution, both from the leadership of each tertiary institution, inadequate use of socialization regarding the Guidance and Counseling Service Unit, budget funds and basic implementation provisions that are not yet adequate and are known to be problems. The low level of student awareness also influences the management of guidance and counseling at each university to be less than optimal. Many students do not take advantage of the guidance program with their respective academic supervisors.